Effect of Temperature and Packaging on Quality of Pigeon Pea Seeds (Cajanus cajan L.) During Storage - Lanchai, Mayura; Rewat Chindachia; Pimpisut Suetrong; Sabaitong Phumkonsan; Chitta Sarpetch; Sopida Sriwilaiwan (Thai Journal of Science and Technology, 2024)
Pigeon pea (Cajanus cajan L.) is a native legume crop with high protein content. It is the main ingredient in a traditional dish in Tak province. A method to maintain the quality of pigeon pea seeds during long-term storage for seed saving and food processing as raw materials were developed. Pigeon pea seeds were stored at 13 and 30 o C using different packaging types including PE (polyethylene) bags, PEA (polyethylene base active) bags and PA/PE (vacuum; polyamide & polyethylene) bags. Seed quality is determined by several factors like seed germination, seed moisture content, seed weight, O2 and CO2 in packaging, insect infestation, seed color (L* C* ho) and seed protein content. Results showed that storing at 13 o C can maintain better quality than storing at 30 o C in all types of packaging, especially storing in PA/PE bags during 12 months of storage, the seed germination rate was high and low insect infestation. This method can be adopted by farmers to extend the shelf life of their pigeon pea seeds.